2001
DOI: 10.1099/00221287-147-2-383
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific inhibition of fungal protein synthesis by sordarin: identification of a sordarin-specificity region in eukaryotic elongation factor 2 The GenBank accession numbers for the sequences reported in this manuscript are AF107286–AF107291, AF292693 and AF248644.

Abstract: The sordarin class of natural products selectively inhibits fungal protein synthesis by impairing the function of eukaryotic elongation factor 2 (eEF2). Mutations in Saccharomyces cerevisiae eEF2 or the ribosomal stalk protein rpP0 can confer resistance to sordarin, although eEF2 is the major determinant of sordarin specificity. It has been shown previously that sordarin specifically binds S. cerevisiae eEF2 while there is no detectable binding to eEF2 from plants or mammals, despite the high level of amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…This indicates that the methylation state of Lys-509 affects the interaction of S. cerevisiae eEF2 with sordarin, and, accordingly, sensitivity toward this drug has been found to be determined by the sequence of amino acids in the "sordarin specificity region" (residues 517-524 in S. cerevisiae eEF2) at the entrance to the sordarin binding cleft (47), which is in close proximity to the Lys-509 in the three-dimensional structure of eEF2 (39).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the methylation state of Lys-509 affects the interaction of S. cerevisiae eEF2 with sordarin, and, accordingly, sensitivity toward this drug has been found to be determined by the sequence of amino acids in the "sordarin specificity region" (residues 517-524 in S. cerevisiae eEF2) at the entrance to the sordarin binding cleft (47), which is in close proximity to the Lys-509 in the three-dimensional structure of eEF2 (39).…”
Section: Discussionmentioning
confidence: 99%
“…Two proteins have been described as targets of sordarin and its derivatives, both involved in protein synthesis: translation elongation factor 2 (eEF2) (5,7,21) and the large ribosomal subunit protein rpP0 (13,22). In the former target, characterization in yeast (Saccharomyces cerevisiae) of spontaneous resistant mutants along with site-directed mutagenesis has been used to identify residues 521, 523, and 524 as the most important amino acids in eEF2 involved in the binding of sordarin (41). Additional residues located at other sites in eEF2 have also been implicated in sordarin resistance (5,21).…”
mentioning
confidence: 99%
“…The ability to inhibit protein synthesis in these organisms correlated well with inhibition of fungal growth and suggests that resistance to sordarins in specific organisms is due to intrinsic differences in the molecular target. Shastry et al [100] isolated and expressed EF2s from various Candida species, including those sensitive and intrinsically resistant to sordarins, in S. cerevisiae. Results from in vitro translation and growth inhibition assays showed that residues in an 8-amino acid region (517-524), in particular residues 521, 523 and 524, within EF2 are responsible for the selectivity of this class of compounds [100].…”
Section: Sordarins and Their Molecular Target Elongation Factor 2 (Ef2)mentioning
confidence: 99%
“…Shastry et al [100] isolated and expressed EF2s from various Candida species, including those sensitive and intrinsically resistant to sordarins, in S. cerevisiae. Results from in vitro translation and growth inhibition assays showed that residues in an 8-amino acid region (517-524), in particular residues 521, 523 and 524, within EF2 are responsible for the selectivity of this class of compounds [100]. The difference between S. cerevisiae and the human in the corresponding residues likewise accounts for the insensitivity of the human protein to sordarins, a conclusion that could not have been reached without the precise molecular details afforded by S. cerevisiae.…”
Section: Sordarins and Their Molecular Target Elongation Factor 2 (Ef2)mentioning
confidence: 99%